Solubilization of silicate from quartz mineral by potential silicate solubilizing bacteria (Pelarutan silika asal mineral kuarsa oleh bakteri pelarut silika potensial ) - Laksmita Prima SANTI; Didiek Hadjar GOENADI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2017)
Silicon (Si) is the second most abundant materials, existing as a compound of several minerals in the soil varies from 50 to 400 g Si per kg of soil. Silicon has positive influence on the plant resistance to various abiotic and biotic stressors such as salinity, drought, heavy metal toxicities and diseases. Although Si is abundant in soil, most of its sources are not available for plant uptake due to low solubility of Si compounds in soil. To improve plant-available Si in the soil, silicate solubilizing bacteria (SSB) are potentially important in solubilizing insoluble forms of silicate. The objectives of this study were to determine: (i) biochemical characteristics of SSB, and (ii) silicate solubilizing activity of Burkholderia cenocepacia KTG, Aeromonas punctata RJM3020, and B. vietnamiensis ZEO3 in magnesium trisilicate (2MgO·3SiO2) and quartz mineral. A laboratory study was conducted at Microbiology and Environment Laboratory, the Indonesian Research Institute for Biotechnology and Bioindustry, Bogor, in 2016. All SSB were grown on Bunt and Rovira media containing 0.25% magnesium trisilicate or quartz mineral as substrate, respectively. Silica solubilizing activities by SSB were determined by using inductively coupled plasma-atomic emission spectrometry while organic acid concentration in the culture were measured by using high-performance liquid chromatography (HPLC). The results indicate that no correlation between solubilizing silicate activity and clear zone on solid Bunt and Rovira media. B.cenocepacia KTG, A.punctata RJM 3020, and B. vietnamiensis ZEO3 isolates were capable of producing citric, acetic, and oxalic acid in various optimum incubation time and accelerating the solubilization of SiO2 originated from quartz with Si solubility at 96-hour incubation time are 0.76; 0.86; and 0.70 ppm respectively. [Key words: Silicate solubilizing bacteria (SSB); Burkholderia cenocepacia KTG, A. punctata RJM 3020, B. vietnamiensis ZEO3, and silisic acid]. Abstrak Silika (Si) merupakan unsur kedua paling banyak dijumpai di dalam tanah dengan konsentrasi yang sangat beragam antara 50-400 g Si per kg tanah. Silika memberikan pengaruh positif pada ketahanan tanaman terhadap berbagai cekaman abiotik dan biotik seperti salinitas, kekeringan, toksisitas logam berat, dan penyakit. Meskipun berlimpah, sebagian besar sumber Si tidak tersedia bagi tanaman, karena kelarutan senyawa Si di dalam tanah cukup rendah. Untuk meningkatkan kelarutan Si di dalam tanah, bakteri pelarut silika berperan penting melarutkan silika dalam bentuk tidak larut. Penelitian ini bertujuan untuk menetapkan: (i)karakterisasi secara biokimia bakteri pelarut silika, dan (ii) kemampuan melarutkan silika dari sumber magnesium trisilika dan mineral kuarsa oleh Burkholderia cenocepacia KTG, Aeromonas punctata RJM3020, dan B. vietnamiensis ZEO3. Kegiatan penelitian dilakukan di Laboratorium Mikrobiologi dan Lingkungan, Pusat Penelitian Bioteknologi dan Bioindustri Indonesia, Bogor, tahun 2016. Bakteri pelarut silika potensial ditumbuhkan di dalam medium Bunt dan Rovira yang mengandung masing-masing 0, 25% magnesium trisilikat atau kuarsa sebagai substrat. Aktivitas pelarutan silika oleh bakteri pelarut silika ditetapkan dengan spektrofotometer emisi atom dan produksi asam organik diukur dengan kromatografi cair kinerja tinggi (HPLC). Hasil penelitian ini menunjukkan bahwa tidak ada korelasi antara aktivitas pelarutan silika dengan zona jernih yang terbentuk dalam medium padat Bunt dan Rovira. Isolat B. cenocepacia KTG, A. punctata RJM3020, dan B. vietnamiensis ZEO3 dapat menghasilkan asam sitrat, oksalat, dan asetat dengan waktu inkubasi optimum yang bervariasi. Ketiga isolat tersebut juga dapat melarutkan SiO2 yang berasal dari mineral kuarsa dengan nilai kelarutan Si pada inkubasi 96 jam masing-masing sebesar 0,76;0,86; dan 0,70 ppm. [Kata kunci: bakteri pelarut silika, Burkholderia cenocepacia KTG, A. punctata RJM 3020, B. vietnamiensis ZEO3, asam silikat.]